Japan-South Korea Relations - a downward spiral: More than "just" historical issues - Alexandra Sakaki (Stiftung Wissenschaft und Politik (SWP), 2019)
The latest dispute between Japan and South Korea over compensation for former Korean forced labourers appears to be following a familiar pattern. Historical spats between two most important democracies in Northeast Asia - especially over the phase of Japanese colonial rule - are nothing new. But the tensions run deeper this time, and mutual mistrust has hit unseen heights. Japanese frustration has grown markedly, with Tokyo feeling duped by Seoul. While there have always been tussles over diverging interpretations of history, current domestic and regional developments are an exacerbating factor. Now leaders in both capitals are publicly questioning whether the other side still shares similar core values and strategic goals. The growing rift could easily affect the regional balance of power, weakening America's position as ally of both Japan and South Korea.
Keywords: 320